Cuantificación de la producción de metabolitos secundarios de Streptomyces sp., bajo estrés inducido por peróxido de hidrógeno, mediante HPLC-DAD. - Romero Luzuriaga, Daniela Cecibel (2014)
The cultivation of Streptomyces through maceration in AcOEt and Amberlite® XAD-7HP obtained with a performance of 0.05%, which was fractionated by chromatography on Sephadex LH-20 using two different mixtures of solvents. Kinetic parameters were evaluated: volumetric speed and specific growth (μmax) reaches its maximum value at 48 hours, while 96 hours get maximum metabolic production with a slow generation time of 51 hours. In the toxicity test with H2O2 wasn’t revealed significant differences in biomass production of the culture, but there was a drastic decrease in the production of secondary metabolites. The total extract showed important activity against E. faecalis (CMI 0,78 μg/mL), as well the F2 fraction (CMI 0,19 μg/mL). It established an easy method to quantitatively detect metabolites present in the extracts and fractions of interest of Streptomyces by HPLC-DAD, the efficiency of this method allowed to obtain defined peaks at different retention times.